Scientific substantiation of the state land cadastre improvement in Ukraine: theoretical and methodological principles - Dorosh, I.; Ibatullin, Sh.; Tarnopolskyi, A.; Dorosh, O. (Land Management, Cadastre and Land Monitoring, 2020)
Based on the fulfilled researches, it was found that the state land cadastre system’s fullness with respect to the land cadastre objects envisaged by the legislation does not meet the modern needs, which does not allow state and local governmental bodies, individuals and legal entities to make management decisions at the appropriate levels. Two of the most difficult problems are the absence of institutions of scientific cadastre support among the cadastre institutions and the removal of territorial communities as consumers and customers of land cadastral information from the land cadastre. It is revealed that the cadastre information contains a large number of errors and inaccuracies, and its structure, organizational and legal frameworks, and information processes require significant improvement. In view of this, the authors present proposals to correct deficiencies in the functioning of the land cadastre system on the basis of complex scientific research of lands of institutions, organizations and enterprises of NAAS. These proposals include improvement of the methodology of the land cadastre maintenance, of the methods, rules, standards and classifiers used in land management and cadastre in current economic conditions; restoration of the state statistical report on land resources in the cadastre; development of information and analytical support for managing land resources at different levels through appropriate electronic offices; cadastre development as a basis for national geospatial data infrastructure. Particular attention is paid to the application of scientific principles in conducting the land cadastre (completeness, mirror image, trust, insurance, continuity, consent, publicity) in the light of world trends. Keywords: state land cadastre, scientific substantiation, principles, methodology of land cadastre management, mistakes, inaccuracies